Perlindungan Hukum Terhadap Pendidik Dalam Penyelenggaraan Pendidikan - Mia Kusuma Fitriana (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2016)
Appealing cases towards teachers are recently became controversy within educational sphere. Teacher and so it called often got reported by the parent on behalf of the student of conducting violence toward their student during the school hours. Meanwhile regulations related to the protection of teacher conducting their professionals duties are already mentioned and stipulated within the Law and Act. And irony occur, even though those legal instruments already regulated but the Police department seems reluctant to use those regulation to prevent teachers from criminalized. Therefore in this writing will be deeply analyzed the legal protection that will work effectively in order to provide legal protection towards teachers and other educators in running their professional duties.